Pengaruh Suhu Pasteurisasi Dengan Menggunakan Metode Ohmic Heating Terhadap Karakteristik Minuman Fungsional Sari Buah Jeruk Lemon - ikrawan, yusep; Rukmamana, Jaka; Gozali, Thomas; Triani, Rini; Salam, Wildan Qoharisma (Politeknik Negeri Lampung., 2023)
The purpose of this study was to determine the effect of temperature on the pasteurization process of ohmicheating method on chemical, physical, microbiological, and ogranoleptic characteristics of lemon juice. Thisstudy used a simple linear regression method with application SPSS version 25. Simple linear regression testdecision making can refer to two things, namely comparing the significance value with the probability value of5%. The response in this study includes the chemical response is protein levels. Physical responses carried outinclude color using colorimetric methods, viscosity, and specific gravity. Microbiological responses include totalplate count (TPC). Organoleptic response is a hedonic test of aroma, taste, and aftertaste. Based on the results of the study, it shows that there is an influence of temperature on the characteristics of lemon juice that has beenpasteurized on the Line Process machine using the ohmic heating method, namely protein content, viscosity, specific gravity, color, and total microbes. Temperature also affects the level of preference for organolepticresponses to the attributes of aroma, taste, and aftertaste.